2002
DOI: 10.2174/1568007023339166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuronal Nicotinic Acetylcholine Receptors in Acute and Chronic Neurodegeneration

Abstract: In the last five years there has been a rapid explosion of publications reporting that neuronal nicotinic acetylcholine receptors (nAChRs) play a role in neurodegenerative disorders. Furthermore, there is a well-established loss of nAChRs in post-mortem brains from patients with Alzheimer's disease, Parkinson's disease and a range of other disorders. In the present review we discuss the evidence that nicotine and subtype selective nAChR ligands can provide neuroprotection in in vitro cell culture systems and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 105 publications
(165 reference statements)
4
128
0
Order By: Relevance
“…Involvement in neuroprotection Nicotine and other nAChR agonists are neuroprotective in several models of neuronal death, both in vivo and in vitro [81] . The nAChRmediated neuroprotection against excitotoxicity is calciumdependent [82][83][84] and does not involve blockade of glutamate receptor function [83][84][85] .…”
Section: Instantaneous Effectsmentioning
confidence: 99%
“…Involvement in neuroprotection Nicotine and other nAChR agonists are neuroprotective in several models of neuronal death, both in vivo and in vitro [81] . The nAChRmediated neuroprotection against excitotoxicity is calciumdependent [82][83][84] and does not involve blockade of glutamate receptor function [83][84][85] .…”
Section: Instantaneous Effectsmentioning
confidence: 99%
“…Extensive evidence using culture systems has shown that nicotine protects against toxicity mediated by β-amyloid, glutamate, ethanol, trophic factor deprivation, arachidonic acid and others [11,[18][19][20]. Of more direct relevance are studies using cultured ventral mesencephalic dopaminergic neurons which show that nicotine pre-treatment attenuates toxicity-induced by MPP + , the metabolite of MPTP that selectively destroys dopaminergic terminals [21].…”
Section: Nicotine-mediated Protection Against Toxic Insults In Culturmentioning
confidence: 99%
“…This may indicate that the loss of receptors in basal ganglia and cortical regions is partly a consequence of deafferentation from midbrain nuclei. Since there is evidence for a neuroprotective role of both the noradrenergic (Martel et al 1998) and the cholinergic (O'Neill et al 2002) system, the loss of receptors might aggravate the damage caused by excitotoxic glutamatergic flow of cortical projection neurones, which in turn is triggered by the high neocortical load of mutant huntingtin (Cepeda et al 2003).…”
Section: Regional Pattern Of Receptor Changesmentioning
confidence: 99%